Empowering global water governance: taking the 2023 UN Water Conference outcomes forward to address the current water crises - Herrfahrdt-Pahle, Elke; Houdret, Annabelle; Dombrowsky, Ines; Cullmann, Johannes; Mukherji, Aditi; Unver, Olcay; Varady, Robert (Informa UK Limited, 2025)
The planet-wide water crisis manifests itself in limited access, overuse, pollution, droughts and flooding. It requires recognizing water as a global commons and improving global water governance. To achieve this, the UN as the only inclusive and global platform for policy development needs increased political commitment and lasting support.